High-peel-strength and high-heat-resistance battery diaphragm, preparation method thereof and secondary battery

By coating a self-assembled coating on the surface of the porous substrate of the sodium ion battery separator, the porous network structure of self-assembled fibers and heat-resistant particles is used to solve the problem of peeling off and powder loss of the ceramic coating, and the peel strength and heat resistance of the separator are improved.

CN119601904AActive Publication Date: 2025-03-11SHENZHEN ZHONGXING NEW MATERIAL TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411506181.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

After long-term use of existing sodium ion battery separators, the ceramic coating is prone to falling off and powder, resulting in insufficient peeling strength and heat resistance.

Method used

A porous substrate is used as the basis and the surface is coated with a self-assembled coating, which consists of self-assembled fibers and heat-resistant particles, which are filled in a porous network composed of self-assembled fibers.

Benefits of technology

It improves the peel strength and heat resistance of the diaphragm, prevents the coating from falling off and powder loss, ensures the dimensional stability of the diaphragm and efficient electrolyte transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601904A_ABST
    Figure CN119601904A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragms, in particular to a high-peel-strength and high-heat-resistance battery diaphragm and a preparation method thereof and a secondary battery, the battery diaphragm comprises a porous base material and a self-assembly coating arranged on at least one surface of the porous base material, and the self-assembly coating comprises self-assembly fibers and heat-resistant particles, a porous network formed by the self-assembly fibers is filled with the heat-resistant particles, and the self-assembly fibers are mainly formed by self-assembly polymerization of a plurality of nanofibers. A framework structure filled with heat-resistant particles is formed by self-assembled fibers formed by polymerization of a plurality of nanofibers, the mechanical strength and thermal stability of the self-assembled fibers can be improved, and a porous network structure composed of the self-assembled fibers enables the coating and the porous base material to have good binding force. And the self-assembled fibers and the heat-resistant particles also have better binding force, so that the peel strength of the coating can be improved, the size stability of the diaphragm is effectively ensured, and the heat resistance of the diaphragm is improved, thereby solving the problem of coating falling or powder falling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and more specifically to a high peel strength and high heat resistance battery separator, a preparation method thereof, and a secondary battery. Background Art

[0002] Sodium-ion batteries mainly consist of a positive electrode, electrolyte, negative electrode, and separator. The separator is known as the third "electrode material" in the battery, which shows that the separator is a key component of sodium-ion batteries. The functions of the separator in sodium-ion batteries include: (1) isolating the positive and negative electrodes to prevent the active materials of the positive and negative electrodes from contacting each other and preventing short circuits inside the battery; (2) maintaining sufficient electrolyte and serving as a transmission channel for sodium ions during charging and discharging, while the separator itself does not participate in any battery reaction.

[0003] At present, the commonly used sodium-ion battery separators are polyolefin separators or ceramic-coated separators. Compared with polyolefin separators, ceramic-coated separators can improve the heat resistance and electrolyte wetting performance of separators to a certain extent. However, after long-term use, the ceramic coating will have the risk of falling off and powdering.

[0004] Therefore, how to improve the peel strength and heat resistance of the separator is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The present application provides a high peel strength and high heat resistance battery separator and a preparation method thereof and a secondary battery, wherein the coating is not easy to shed and fall off, and the peel strength and heat resistance of the separator can be improved.

[0006] The present application provides a high peel strength and high heat resistance battery separator, comprising a porous substrate and a self-assembled coating arranged on at least one surface of the porous substrate, the self-assembled coating comprising self-assembled fibers and heat-resistant particles, the heat-resistant particles are filled in the porous network formed by the self-assembled fibers, and the self-assembled fibers are mainly formed by self-assembly polymerization of multiple nanofibers.

[0007] In an optional embodiment, the diameter of the self-assembled fiber ranges from 100 nm to 1000 nm.

[0008] In an optional embodiment, the nanofiber satisfies at least one of the conditions (1)-(3):

[0009] (1) The nanofiber is a heat-resistant nanofiber, and the nanofiber includes at least one of nanocellulose, aramid nanofiber and polyimide nanofiber;

[0010] (2) The diameter of the nanofibers ranges from 3 nm to 25 nm;

[0011] (3) The length of the nanofibers ranges from 100 nm to 1000 nm.

[0012] In an optional embodiment, the nanofibers are heat-resistant nanofibers with hydrophobic surface modification;

[0013] Optionally, the heat-resistant nanofiber is made of nanocellulose.

[0014] In an optional embodiment, the heat-resistant particles meet at least one of the conditions (1)-(2):

[0015] (1) The heat-resistant particles include inorganic particles, and the inorganic particles include at least one of aluminum oxide, magnesium oxide, silicon dioxide, calcium oxide, titanium oxide, aluminum hydroxide, magnesium hydroxide, magnesium sulfate, calcium sulfate, barium sulfate, calcium carbonate, boehmite, aluminum nitride and titanium nitride;

[0016] (2) The particle size D50 of the heat-resistant particles ranges from 100 nm to 1000 nm.

[0017] In an optional embodiment, the self-assembling coating satisfies at least one of the conditions (1)-(6):

[0018] (1) In the self-assembling coating, the mass ratio of the self-assembling fibers to the heat-resistant particles is 1:3-1:15;

[0019] (2) In the self-assembled coating, the mass percentage of the self-assembled fibers is 5%-25%;

[0020] (3) In the self-assembled coating, the mass percentage of the heat-resistant particles is 65%-85%;

[0021] (4) The self-assembly coating further comprises a binder and a dispersant;

[0022] Wherein, the mass percentage of the binder is 5%-15%, and / or the mass percentage of the dispersant is 0.5%-2%;

[0023] (5) The self-assembled coating is prepared by spraying, roller coating, spot coating or dip coating;

[0024] (6) The thickness of the self-assembled coating ranges from 0.5 μm to 8 μm.

[0025] In an optional embodiment, the battery separator satisfies at least one of the conditions (1)-(5):

[0026] (1) The coating permeability value of the battery separator is ≤100s / 100mL;

[0027] (2) The thermal shrinkage rate of the battery separator in the MD direction after being treated at 180° C. for 1 hour is ≤5%;

[0028] (3) The porous substrate comprises at least one of a polyethylene film, a polypropylene film, a polyimide film, a polyvinylidene fluoride film, a polyvinylidene fluoride-hexafluoropropylene film, a polyamide film and a polyethylene terephthalate film;

[0029] (4) The thickness of the porous substrate ranges from 5 μm to 25 μm;

[0030] (5) The porosity of the porous substrate ranges from 30% to 65%.

[0031] The present application provides a method for preparing a high peel strength and high heat resistance battery separator, wherein the battery separator is the battery separator as described above, and the steps include:

[0032] Nanofibers and heat-resistant particles are mixed according to a ratio to prepare a self-assembly coating slurry, wherein a plurality of the nanofibers are polymerized and assembled to form self-assembly fibers;

[0033] The self-assembly coating slurry is coated on at least one surface of the porous substrate and dried to obtain a battery separator.

[0034] The nanofibers are nanocellulose with hydrophobic surface modification, and the preparation steps include:

[0035] The pH value of the aqueous dispersion of nanofibers is adjusted to 8-9;

[0036] Adding a buffer and plant polyphenols to the aqueous dispersion after adjusting the pH value, stirring and mixing evenly, adding an ethanol solution of a long-chain alkylamine, and continuing mechanical stirring in a water bath at 45° C. to obtain a mixed solution;

[0037] The mixed solution is centrifuged and washed with ethanol and deionized water to finally obtain the surface hydrophobically modified nanocellulose.

[0038] The present application provides a secondary battery, comprising the battery separator as described above, or a battery separator prepared by the method for preparing the battery separator as described above.

[0039] According to the battery separator in the above embodiment, it includes a porous substrate and a self-assembled coating disposed on at least one surface of the porous substrate, the self-assembled coating includes self-assembled fibers and heat-resistant particles, the heat-resistant particles are filled in the porous network formed by the self-assembled fibers, and the self-assembled fibers are mainly formed by self-assembly polymerization of multiple nanofibers. The self-assembled fibers formed by the polymerization of multiple nanofibers form a porous grid structure as a skeleton structure filled with heat-resistant particles, which can improve the mechanical strength and thermal stability of the self-assembled fibers. At the same time, the porous network structure composed of the self-assembled fibers makes the coating have a better bonding force with the porous substrate, and the self-assembled fibers also have a better bonding force with the heat-resistant particles, which can improve the peeling strength of the coating and effectively ensure the stability of the size of the separator, thereby further improving the heat resistance of the separator, thereby solving the problem of coating shedding or powdering. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of a battery separator structure in an embodiment;

[0041] Figure 2 The figure is a flow chart of the preparation of a battery separator in one embodiment.

[0042] Wherein: 100, self-assembly coating; 110, first self-assembly coating; 120, second self-assembly coating; 200, porous substrate. DETAILED DESCRIPTION

[0043] The present application is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations based on the description in the specification and the general technical knowledge in the art.

[0044] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations, and the operation steps involved in each embodiment can also be replaced or adjusted in a sequence in a manner that is obvious to those skilled in the art. Therefore, the specification and drawings are only for the purpose of clearly describing a certain embodiment and do not mean that the composition and / or sequence are necessary.

[0045] The serial numbers of the components in this document, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning. The "connection" and "coupling" mentioned in this application, unless otherwise specified, include direct and indirect connections (couplings).

[0046] The "diaphragm" referred to in this application is an important component of the secondary battery cell. The diaphragm is a thin film used to separate the positive and negative electrodes during the electrolysis reaction to prevent the loss of energy in the direct reaction. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery.

[0047] Secondary batteries refer to batteries that can be used again by recharging the active materials after the battery is discharged. This type of battery usually uses the reversibility of chemical reactions, that is, after a chemical reaction is converted into electrical energy, the chemical system can be repaired with electrical energy, and then converted into electrical energy by chemical reaction again. Among them, the more common secondary batteries include but are not limited to nickel-metal hydride batteries, nickel-cadmium batteries, lead-acid (or lead storage) batteries, lithium-ion batteries, polymer lithium-ion batteries, sodium-ion batteries, etc.

[0048] The present application discloses a high peel strength and high heat resistance battery separator, which can be applied to secondary batteries, mainly to sodium ion batteries, including a porous substrate 200 and a self-assembled coating 100 disposed on at least one surface of the porous substrate 200, wherein the self-assembled coating 100 includes self-assembled fibers and heat-resistant particles, and the heat-resistant particles are filled in a porous network formed by the self-assembled fibers, and the self-assembled fibers are mainly formed by self-assembly polymerization of multiple nanofibers. In some specific embodiments, such as Figure 1 The two surfaces of the porous substrate 200 are provided with self-assembly coatings 100, including a first self-assembly coating 110 and a second self-assembly coating 120. In specific implementation, since the two surfaces of the diaphragm correspond to the positive electrode or the negative electrode in the battery, the first self-assembly coating 110 and the second self-assembly coating 120 are connected to the positive electrode or the negative electrode respectively, and the properties of the first self-assembly coating 110 and the second self-assembly coating 120 can be slightly different. For example, the thickness of the first self-assembly coating 110 and the second self-assembly coating 120 and the mass ratio of the components can be adjusted according to the situation. Of course, in other embodiments, the self-assembly coating 100 can also be provided on one of the surfaces of the porous substrate 200.

[0049] In the present application, multiple nanofibers are creatively aggregated to form self-assembled fibers, and then the self-assembled fibers are used to form a porous grid structure as a skeleton structure filled with heat-resistant particles. Since the aggregation of multiple nanofibers can improve the mechanical strength of the self-assembled fibers themselves, and since multiple nanofibers are combined through intermolecular forces (mainly hydrogen bonds) to form self-assembled fibers, compared with multiple dispersed nanofibers, the mechanical strength and thermal stability of the self-assembled fibers can be further improved. At the same time, the porous network structure composed of the self-assembled fibers makes the coating have better bonding strength with the porous substrate 200, and the self-assembled fibers also have better bonding strength with the heat-resistant particles, which can improve the peeling strength of the coating and effectively ensure the stability of the size of the diaphragm, thereby further improving the heat resistance of the diaphragm.

[0050] In some embodiments, the porous substrate 200 is at least one of polyethylene film, polypropylene film, polyimide film, polyvinylidene fluoride film, polyvinylidene fluoride-hexafluoropropylene film, polyamide film and polyethylene terephthalate film, and the material preparation process is mature, so that the preparation cost is controllable. At the same time, the material of the porous substrate 200 has good processing performance, and under the premise of a small thickness, it also has high strength and heat resistance, which helps the diaphragm to have both low thickness and high heat resistance, and is conducive to the secondary battery having high energy density, good processing performance and high reliability.

[0051] In some embodiments, the porous substrate 200 has a thickness of 5 μm to 25 μm. For example, the porous substrate 200 has a thickness of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 15 μm, 20 μm, or 25 μm.

[0052] In some embodiments, the porosity of the porous substrate 200 is 30%-65%. For example, the porosity of the porous substrate 200 is 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%. The porosity of the porous substrate 200 has a well-known meaning in the art and can be measured by methods known in the art. For example, it can be tested with reference to GB / T 36363-2018.

[0053] In some embodiments, the diameter of the self-assembled fibers ranges from 100 nm to 1000 nm. The diameter of the self-assembled fibers reaches the micrometer level, which can be observed under a scanning electron microscope at a magnification of 10,000 to 20,000 times the surface of the diaphragm coating. Compared with dispersed nanofibers, the above-mentioned micrometer-sized self-assembled fibers can improve the overall mechanical strength of the coating, and make the combination between the heat-resistant particles and the self-assembled fibers better, which can improve the peel strength of the coating.

[0054] In some embodiments, the nanofibers are heat-resistant nanofibers, and the nanofibers include at least one of nanocellulose, aramid nanofibers, and polyimide nanofibers. The heat-resistant nanofibers have good heat resistance, and the self-assembled fibers composed of them serve as the skeleton structure in the self-assembled coating 100 of the diaphragm, which can improve the heat resistance of the diaphragm. Compared with plant fibers, the nanofibers used in this application have a larger specific surface area and rich surface functional groups, are easy to disperse into an aqueous slurry (better processing performance), and exhibit certain bonding properties. The coating formed with the inorganic filler is more stable. At the same time, the nanofibers have better high temperature resistance and can withstand high temperatures greater than 200°C, which can further improve the heat resistance of the diaphragm.

[0055] Specifically, nanocellulose includes but is not limited to cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs), bacterial cellulose (BC), etc. Aramid nanofibers can be selected from meta-aramid nanofibers and para-aramid nanofibers.

[0056] In some embodiments, the diameter of the nanofiber ranges from 3nm to 25nm. For example, the diameter of the nanofiber is 3nm, 4nm, 5nm, 10nm, 15nm, 20nm or 25nm. Optionally, the diameter of the nanofiber ranges from 4nm to 10nm. By adjusting the average diameter of the nanocellulose within the above range, it is beneficial for the nanocellulose to polymerize to form self-assembled fibers with higher strength, and it is also beneficial for the self-assembled fibers formed by the polymerization to overlap to form a three-dimensional porous grid structure, and it is also beneficial for the three-dimensional porous grid structure formed to overlap with the granular heat-resistant particles to form an integrated coating, which is beneficial to improve the heat resistance of the diaphragm, and then to improve the performance of the secondary battery.

[0057] In some embodiments, the length of the nanofiber ranges from 100nm to 1000nm. For example, the length of the nanofiber is 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm. Optionally, the diameter of the nanofiber ranges from 100nm to 500nm. By adjusting the average length of nanocellulose within the above range, it is beneficial for nanocellulose to polymerize to form self-assembled fibers with higher strength, and it is also beneficial for the self-assembled fibers formed by its polymerization to overlap to form a three-dimensional porous grid structure, and it is also beneficial for the three-dimensional porous grid structure formed to overlap with the granular heat-resistant particles to form an integrated coating, so as to improve the heat resistance of the diaphragm, and then to improve the performance of the secondary battery. By adjusting the average length of nanocellulose within the above range, it is also beneficial for the coating slurry to have a suitable viscosity, which is beneficial for coating, and it is also beneficial for improving the uniformity and consistency of the coating.

[0058] In some embodiments, in order to further effectively improve the performance of the diaphragm, the nanofibers are heat-resistant nanofibers with hydrophobic surface modification. Specifically, by depositing a hydrophobic modifier on the surface of the nanofibers, the aggregation between the fibers can be promoted, so that the fibers can self-assemble through intermolecular forces (mainly hydrogen bonding) to form an externally hydrophobic self-assembled fiber structure, thereby improving the peel strength and thermal dimensional stability of the diaphragm coating, and reducing the moisture content of the diaphragm. The hydrophobic modifier includes plant polyphenols and long-chain alkylamines.

[0059] In some embodiments, the heat-resistant particles include inorganic particles, and the inorganic particles include at least one of aluminum oxide, magnesium oxide, silicon dioxide, calcium oxide, titanium oxide, aluminum hydroxide, magnesium hydroxide, magnesium sulfate, calcium sulfate, barium sulfate, calcium carbonate, boehmite, aluminum nitride, and titanium nitride. The heat-resistant particles have good thermal stability, and the porous network formed by the self-assembled fibers is used as a skeleton to fill in the gaps of the self-assembled fibers, so that the uniformity of the coating is good, and the heat resistance of the diaphragm can be further improved.

[0060] In some embodiments, the particle size D50 of the heat-resistant particles ranges from 100nm to 1000nm. For example, the particle size D50 of the heat-resistant particles is 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm. Optionally, the particle size D50 of the heat-resistant particles ranges from 300nm to 600nm. By controlling the average particle size of the heat-resistant particles within the above range, the pore structure of the diaphragm can be effectively retained, providing a channel for ion transmission, and the selection of heat-resistant particles of this particle size can improve the strength of the coating, thereby improving the overall mechanical strength of the diaphragm.

[0061] In some embodiments, in the self-assembling coating 100, the mass ratio of the self-assembling fibers to the heat-resistant particles is 1:3-1:15. For example, the mass ratio of the self-assembling fibers to the heat-resistant particles is 1:3, 1:5, 1:10, 1:12 or 1:15. The mass ratio of the self-assembling fibers to the heat-resistant particles is controlled within the above range, which is beneficial to improving the mechanical strength of the coating, and is also beneficial to improving the adhesion of the coating, improving its peel strength, so as to improve the stability of the diaphragm structure, and is also beneficial to the coating of the coating slurry, so that the coating has good consistency and uniformity.

[0062] In some embodiments, in the self-assembling coating 100, the mass percentage of the self-assembling fibers is 5%-25%. For example, the mass percentage of the self-assembling fibers is 5%, 10%, 15%, 20% or 25%.

[0063] In some embodiments, in the self-assembling coating 100, the mass percentage of the heat-resistant particles is 65%-85%. For example, the mass percentage of the heat-resistant particles is 65%, 70%, 75%, 80% or 85%.

[0064] In some embodiments, the self-assembly coating 100 further includes a binder and a dispersant. The setting of the binder enhances the bonding force between the components, which is beneficial to improving the mechanical strength and peel strength of the coating. The setting of the dispersant is beneficial to the uniformity of the coating slurry, thereby improving the consistency of the coating.

[0065] In some embodiments, the mass percentage of the binder is 5%-15%. For example, the mass percentage of the binder is 5%, 6%, 7%, 8%, 9%, 10%, 12% or 15%.

[0066] In some embodiments, the mass percentage of the dispersant is 0.5%-2%. For example, the mass percentage of the dispersant is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5% or 2%.

[0067] In some embodiments, the self-assembling coating 100 is prepared by spray coating, roller coating, spot coating or dip coating.

[0068] In some embodiments, the thickness of the self-assembled coating 100 is 0.5 μm-8 μm. For example, the thickness of the self-assembled coating 100 is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm. Optionally, the thickness of the self-assembled coating 100 is 0.5 μm-4 μm. The thickness control of the self-assembled coating 100 can effectively improve the strength and heat resistance of the diaphragm and realize the minimum thickness design of the diaphragm, which is conducive to the realization of high energy density of secondary batteries.

[0069] In some embodiments, the coating permeability increment of the battery separator is ≤100s / 100mL. The coating permeability increment is controlled within the above range, so that the separator has better ion transmission performance, which is beneficial to improving the performance of the secondary battery.

[0070] In some embodiments, the thermal shrinkage rate of the battery separator in the MD direction after being treated at 180° C. for 1 hour is ≤5%. The thermal shrinkage rate of the battery separator is within the above range, so that the separator has good thermal stability and good heat resistance.

[0071] See also Figure 2 The present application also provides a method for preparing a battery separator, and the steps for preparing the above-mentioned battery separator include:

[0072] S101, mixing nanofibers and heat-resistant particles according to a ratio to prepare a self-assembled coating slurry, wherein a plurality of nanofibers are polymerized and assembled to form self-assembled fibers.

[0073] Specifically, after the nanofibers and heat-resistant particles are mixed, a self-assembled coating slurry can be formed. Multiple nanofibers can eventually be assembled into self-assembled fibers with a porous grid structure. The heat-resistant particles are filled in the porous grid of the self-assembled fibers. The self-assembled fibers formed by the polymerization of multiple nanofibers have a micron-level size, which can effectively improve the mechanical strength and heat resistance of the diaphragm.

[0074] S102 , coating the self-assembly coating slurry on at least one surface of the porous substrate 200 , and drying to obtain a battery separator.

[0075] Specifically, the self-assembled fibers and heat-resistant particles are mixed in a ratio to prepare a coating slurry with good uniformity, and then a preparation process such as spraying, roller coating, spot coating or dip coating is used to uniformly coat at least one surface of the porous substrate 200 to form a coating, and after baking, a battery separator with high peel strength and high heat resistance is obtained.

[0076] In some embodiments, before step S101, the nanofibers are subjected to hydrophobic modification to obtain hydrophobically modified nanofibers, and the specific steps include: adjusting the pH value of the aqueous dispersion of the nanofibers to 8-9; adding a buffer and plant polyphenols to the aqueous dispersion after adjusting the pH value, stirring and mixing evenly, and adding an ethanol solution of a long-chain alkylamine, and continuing mechanical stirring under a 45°C water bath to obtain a mixed solution; the mixed solution is centrifuged and washed with ethanol and deionized water to finally obtain surface hydrophobically modified nanocellulose. The long-chain alkylamine can specifically be hexadecylamine or octadecylamine. The plant polyphenols include one or more of gallic acid, methyl gallate, ethyl gallate, propyl gallate and protocatechuic acid. Among them, in the ethanol solution of the long-chain alkylamine, the mass fraction of the long-chain alkylamine is 1%-3%.

[0077] For example, taking nanocellulose (CNFs) as an example, the pH value of 100g of CNFs aqueous dispersion with a mass fraction of 3%-8% is adjusted to 8-9 with NaOH solution, 0.4g of tris (hydroxymethyl) aminomethane (Tris) is added to the CNFs dispersion as a buffer, and then 0.4g-2g of plant polyphenols are added, and mechanical stirring is carried out at room temperature at a speed of 400r / min for 8h. Prepare 100g of 1%-3% octadecylamine (ODA) ethanol solution, mix it with the above solution, continue mechanical stirring for 8h under 45℃ water bath conditions, and the resulting product is centrifuged and washed with ethanol and deionized water in turn, and finally obtain hydrophobically modified CNFs. The hydrophobicity of the surface of CNFs modified by plant polyphenols and long-chain alkylamines increases, and can promote the aggregation and bonding between nanofibers, which is conducive to the assembly of nanofibers to form self-assembled fibers with surface hydrophobic groups.

[0078] Among them, the plant polyphenols include at least one of gallic acid (GA), methyl gallate (MG), ethyl gallate (EG), propyl gallate (PG) and protocatechuic acid (PCA).

[0079] The present application also provides a secondary battery, comprising the above-mentioned battery separator, or the battery separator prepared by the above-mentioned preparation method.

[0080] The technical solution of the present application is further described below through specific embodiments.

[0081] Embodiment 1

[0082] Preparation of hydrophobically modified nanocellulose: The pH value of 100g of CNFs (diameter 4nm-10nm, length 100nm-500nm) aqueous dispersion with a solid content of 4% was adjusted to 8-9 with a 0.1% NaOH aqueous solution, 0.4g Tris was added to the CNFs dispersion as a buffer, and then 0.4g propyl gallate was added, and mechanical stirring was carried out at room temperature for 8h at a speed of 400r / min. 100g of 2% octadecylamine (ODA) or ethanol solution was prepared, mixed with the above solution, and mechanical stirring was continued for 8h under 45°C water bath conditions. The obtained product was centrifuged and washed with ethanol and deionized water in turn, and finally hydrophobically modified CNFs were obtained. The hydrophobically modified CNFs were dispersed in an ethanol / water mixed solvent (the mass ratio of ethanol to water was 1:2) to prepare a hydrophobically modified CNFs dispersion with a solid content of 4%.

[0083] Preparation of coating slurry: Mix 75g of alumina particles (D50 is 400nm), 1g of dispersant and 24g of deionized water, then add a hydrophobically modified CNFs dispersion with a solid content of 4% according to a CNFs to alumina mass ratio of 1:15, stir evenly, then add 10g of adhesive, continue stirring evenly to obtain a coating slurry.

[0084] Preparation of diaphragm: The above coating slurry was double-sidedly coated on a polypropylene porous membrane (thickness 12 μm, porosity 40%) and dried to obtain the diaphragm of this example.

[0085] Embodiment 2, Embodiment 3

[0086] The difference between Example 2 to Example 3 and Example 1 is that the mass ratio of CNFs to alumina is different.

[0087] Embodiment 4, Embodiment 5

[0088] The difference between the fourth and fifth embodiments and the second embodiment is that the particle size D50 of the aluminum oxide particles is different.

[0089] Embodiment 6

[0090] The difference between this embodiment and the second embodiment is that modified CNFs are not used.

[0091] In this embodiment, the preparation process of the coating slurry is as follows: 75g of alumina particles (D50 = 400nm), 1g of dispersant and 24g of deionized water are mixed and stirred, and NaOH aqueous solution is added to adjust the pH to 8-9 to prepare an alumina dispersion. Then, according to the mass ratio of CNFs to alumina of 1:5, a CNFs (diameter 4nm-10nm, length 100nm-500nm) aqueous dispersion with a solid content of 4% is mixed with the above alumina dispersion, stirred evenly, and then 10g of adhesive is added, and stirring is continued to obtain a coating slurry.

[0092] Comparative Example 1

[0093] The difference between this comparative example and Example 1 is that the coating slurry does not contain CNFs.

[0094] In this comparative example, the preparation process of the coating slurry is as follows: 75 g of alumina particles (D50=400 nm), 1 g of a dispersant and 130 g of deionized water are mixed and stirred, and then 10 g of an adhesive is added and stirred evenly to obtain a coating slurry.

[0095] Comparative Example 2

[0096] The difference between this comparative example and Example 6 is that the preparation steps of the coating slurry are different.

[0097] In this comparative example, the preparation process of the coating slurry is as follows: according to the mass ratio of nanocellulose, alumina particles (D50 = 400nm), dispersant and deionized water of 5g:75g:1g:24g, a CNFs aqueous dispersion with a solid content of 4% (diameter 4nm-10nm, length 100nm-500nm), alumina particles, dispersant and deionized water are mixed and stirred evenly, and then 10g of adhesive is added, and stirring is continued to obtain a coating slurry.

[0098] The battery separator compositions and preparation processes of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 1 below.

[0099] Table 1

[0100]

[0101] The battery separators of the above-mentioned embodiments and comparative examples were tested. The test method is as follows:

[0102] Coating permeability value-added: Cut a 100mm×100mm membrane sample and use the American Gurley 4110N air permeability tester to test it using a 100mL test gas mode. Record the time it takes for the test gas to pass through the membrane sample, which is the air permeability value. The coating permeability value-added is the air permeability value of the membrane with coating minus the air permeability value of the membrane without coating (i.e., pure porous substrate 200).

[0103] Thermal shrinkage: The test method is based on the requirements of GB / T12027-2004. The following steps are included: Cut the diaphragm to a size of 15*15cm, and use a ruler to measure the longitudinal and transverse lengths of the sample on the surface of the diaphragm; use a ruler to measure the longitudinal length of the sample; place the sample flat in a fixture, and then place it in an oven at 180℃ for 1h; after heating, take out the sample, and after returning to room temperature, measure the longitudinal marked length again, calculate the shrinkage rate according to the following formula, and finally take the average value of several samples as the thermal shrinkage rate.

[0104]

[0105] ΔL: thermal shrinkage rate of the sample in the longitudinal direction, expressed in %; L0: length of the sample in the longitudinal direction before heating, in millimeters (mm); L: length of the sample in the longitudinal direction after heating, in millimeters (mm).

[0106] Coating peel strength: Use 3M tape to stick on the coating surface to test the peel strength. The test method refers to the national standard GB / T 2790-1995. After the test, the test data is processed according to the provisions of the national standard GB / T 17200-1998 "Processing of Adhesion Peel Test Data".

[0107] Moisture content: tested using a Karl Fischer moisture tester.

[0108] The test results are shown in Table 2 below.

[0109] Table 2

[0110]

[0111]

[0112] In comparative example 1, nanofibers are not added, and in comparative example 2, nanofibers and heat-resistant particles are directly mixed to prepare a coating. A fine fiber structure can be observed in the coating of comparative example 2, and the diameter of the fiber is less than 100 nm. A coarse fiber structure can be observed in the coatings of embodiments 1 to 6, and the diameter of the fiber is between 100 nm and 1000 nm. It can be seen from the data in Table 2 that, compared with comparative example 2, self-assembled fibers are formed in the coatings of embodiments 1 to 6, which have better heat resistance and coating peeling strength.

[0113] In Examples 1 to 5, hydrophobically modified CNFs were used. Compared with the unmodified CNFs used in Example 6, the diameter of the coated self-assembled fibers was slightly increased. This is because the surface hydrophobic modification can promote the aggregation between fibers. At the same time, the use of hydrophobically modified CNFs in the coating can reduce the water absorption of nanocellulose and reduce the moisture content of the diaphragm.

[0114] The above specific examples are used to illustrate the present application, which is only used to help understand the present application and is not intended to limit the present application. For technicians in the technical field to which the present application belongs, they can also make some simple deductions, deformations or substitutions based on the ideas of the present application.

Claims

1. A high peel strength and high heat resistance battery separator, characterized in that: It includes a porous substrate and a self-assembled coating arranged on at least one surface of the porous substrate, the self-assembled coating includes self-assembled fibers and heat-resistant particles, the heat-resistant particles are filled in the porous network formed by the self-assembled fibers, and the self-assembled fibers are mainly formed by self-assembly polymerization of multiple nanofibers.

2. The high peel strength and high heat resistance battery separator according to claim 1, characterized in that: The diameter of the self-assembled fiber ranges from 100 nm to 1000 nm.

3. The high peel strength and high heat resistance battery separator according to claim 1, characterized in that: The nanofibers satisfy at least one of the conditions (1) to (3): (1) The nanofiber is a heat-resistant nanofiber, and the nanofiber includes at least one of nanocellulose, aramid nanofiber and polyimide nanofiber; (2) The diameter of the nanofibers ranges from 3 nm to 25 nm; (3) The length of the nanofibers ranges from 100 nm to 1000 nm.

4. The high peel strength and high heat resistance battery separator according to claim 1, characterized in that: The nanofibers are heat-resistant nanofibers with hydrophobic surface modification; Optionally, the heat-resistant nanofiber is made of nanocellulose.

5. The high peel strength and high heat resistance battery separator according to any one of claims 1 to 4, characterized in that: The heat-resistant particles meet at least one of the conditions (1)-(2): (1) The heat-resistant particles include inorganic particles, and the inorganic particles include at least one of aluminum oxide, magnesium oxide, silicon dioxide, calcium oxide, titanium oxide, aluminum hydroxide, magnesium hydroxide, magnesium sulfate, calcium sulfate, barium sulfate, calcium carbonate, boehmite, aluminum nitride and titanium nitride; (2) The particle size D50 of the heat-resistant particles ranges from 100 nm to 1000 nm.

6. The battery separator according to any one of claims 1 to 4, characterized in that The self-assembling coating satisfies at least one of the conditions (1) to (6): (1) In the self-assembling coating, the mass ratio of the self-assembling fibers to the heat-resistant particles is 1:3-1:15; (2) In the self-assembled coating, the mass percentage of the self-assembled fibers is 5%-25%; (3) In the self-assembled coating, the mass percentage of the heat-resistant particles is 65%-85%; (4) The self-assembly coating further comprises a binder and a dispersant; Wherein, the mass percentage of the binder is 5%-15%, and / or the mass percentage of the dispersant is 0.5%-2%; (5) The self-assembled coating is prepared by spraying, roller coating, spot coating or dip coating; (6) The thickness of the self-assembled coating ranges from 0.5 μm to 8 μm.

7. The high peel strength and high heat resistance battery separator according to any one of claims 1 to 4, characterized in that: The battery separator satisfies at least one of the conditions (1) to (5): (1) The coating permeability value of the battery separator is ≤100s / 100mL; (2) The thermal shrinkage rate of the battery separator in the MD direction after being treated at 180° C. for 1 hour is ≤5%; (3) The porous substrate comprises at least one of a polyethylene film, a polypropylene film, a polyimide film, a polyvinylidene fluoride film, a polyvinylidene fluoride-hexafluoropropylene film, a polyamide film and a polyethylene terephthalate film; (4) The thickness of the porous substrate ranges from 5 μm to 25 μm; (5) The porosity of the porous substrate ranges from 30% to 65%.

8. A method for preparing a high peel strength and high heat resistance battery separator, wherein the battery separator is the battery separator as claimed in any one of claims 1 to 7, characterized in that: The steps include: Nanofibers and heat-resistant particles are mixed according to a ratio to prepare a self-assembly coating slurry, wherein a plurality of the nanofibers are polymerized and assembled to form self-assembly fibers; The self-assembly coating slurry is coated on at least one surface of the porous substrate and dried to obtain a battery separator.

9. The method for preparing a high peel strength and high heat resistance battery separator according to claim 8, characterized in that: The nanofibers are nanocellulose with hydrophobic surface modification, and the preparation steps include: The pH value of the aqueous dispersion of nanocellulose is adjusted to 8-9; Adding a buffer and plant polyphenols to the aqueous dispersion after adjusting the pH value, stirring and mixing evenly, adding an ethanol solution of a long-chain alkylamine, and continuing mechanical stirring in a water bath at 45° C. to obtain a mixed solution; The mixed solution is centrifuged and washed with ethanol and deionized water to finally obtain the surface hydrophobically modified nanocellulose.

10. A secondary battery, characterized in that: The invention comprises the battery separator according to any one of claims 1 to 7, or the battery separator prepared by the preparation method according to claim 8 or 9.

Citation Information

Patent Citations

  • Composite nanofiber diaphragm for electrochemical element, preparation method and energy storage device

    CN105655526A

  • Battery diaphragm, preparation method thereof and lithium ion battery

    CN114824654A

  • Modified composite diaphragm and preparation method thereof

    CN116315437A

  • Functionalized aramid nanofiber-based battery diaphragm as well as preparation method and application thereof

    CN117013192A

  • Diaphragm, preparation method thereof and secondary battery

    CN117832759A